2018
DOI: 10.1007/s12022-018-9526-7
|View full text |Cite
|
Sign up to set email alerts
|

LIMD2 Is Overexpressed in BRAF V600E-Positive Papillary Thyroid Carcinomas and Matched Lymph Node Metastases

Abstract: We previously described that LIM domain containing 2 (LIMD2) overexpression was closely correlated with metastatic process in papillary thyroid carcinoma (PTC). We here evaluated the expression of LIMD2 in a series of non-metastatic and metastatic PTC and their matched lymph node metastases via immunohistochemistry. LIMD2 was expressed in 74 (81%) of primary PTC and 35 (95%) of lymph node metastases. Sub-analysis performed in 37 matched samples demonstrated that in four cases, LIMD2 is expressed in lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…As a LIM domain protein, LIMD2 has been functionally associated with cell motility and adhesion, mostly by regulating mRNA transcription [ 9 , 31 ]. In our study, we found that LIMD2 was upregulated in OC tissues, which was consistent with the findings in lung cancer [ 11 ] and papillary thyroid cancer [ 10 ]. LIMD2 expression levels were positively correlated with cell motility metastatic potential and grade in both fresh and archived tumors, including bladder melanoma breast and thyroid tumors [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a LIM domain protein, LIMD2 has been functionally associated with cell motility and adhesion, mostly by regulating mRNA transcription [ 9 , 31 ]. In our study, we found that LIMD2 was upregulated in OC tissues, which was consistent with the findings in lung cancer [ 11 ] and papillary thyroid cancer [ 10 ]. LIMD2 expression levels were positively correlated with cell motility metastatic potential and grade in both fresh and archived tumors, including bladder melanoma breast and thyroid tumors [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, LIMD2 plays an important role in tumorigenesis and development. It has been reported that LIMD2 was a lymph node metastasis marker for papillary thyroid carcinoma (PTC) [ 10 ]. Also, LIMD2 was found to be overexpressed in most metastatic lymph nodes in PTC, while it was undetectable or expressed at relatively low levels in the primary PTCs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For amplification of exon 15 of BRAF , the PCR protocol was performed as previously described: an initial denaturation step at 94°C for 5 min followed by 40 cycles of a three-step program, namely, 94°C for 30 s, 53°C for 40 s and 72°C for 30 s, and a final 2-min extension at 72°C (37). For amplification of exon 2 of NRAS or HRAS , the amplification protocol was an initial denaturation step at 94°C for 5 min followed by 40 cycles of a three-step program, namely, 94°C for 30 s, 56°C for 45 s and 72°C for 45 s, and a final 7-min extension at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…Hence a total of 115 thyroid specimens were analysed. As controls, we additionally included FFPE from thyroid samples that had previously been confirmed as positive (PTC) and negative (FTA) for BRAF V600E mutation by Sanger Sequencing 20 22 . The study was conducted under the approval of the Research Ethical Committee of the Universidade Federal de São Paulo, São Paulo, Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…All samples with less than 20% abundance of the BRAF V600E mutated allele by pyrosequencing were screened by sequenced by Sanger Sequencing as previously described 20 22 . Additionally, we randomly selected samples with > 20% of abundance of mutated alleles for Sanger Sequencing.…”
Section: Methodsmentioning
confidence: 99%